2014
DOI: 10.5194/cp-10-79-2014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the dominant components of warming in Pliocene climate simulations

Abstract: Abstract. The Pliocene Model Intercomparison Project (PlioMIP) is the first coordinated climate model comparison for a warmer palaeoclimate with atmospheric CO 2 significantly higher than pre-industrial concentrations. The simulations of the mid-Pliocene warm period show global warming of between 1.8 and 3.6 • C above pre-industrial surface air temperatures, with significant polar amplification. Here we perform energy balance calculations on all eight of the coupled ocean-atmosphere simulations within PlioMIP … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 45 publications
10
60
0
Order By: Relevance
“…In response to the greenhouse-gas-driven warming seen in the Pliocene experiments (Hill et al, 2014), a general decrease is observed in genesis potential in the convergence zones in both the Northern and Southern Hemispheres (Fig. 7, 8b).…”
Section: Discussionmentioning
confidence: 99%
“…In response to the greenhouse-gas-driven warming seen in the Pliocene experiments (Hill et al, 2014), a general decrease is observed in genesis potential in the convergence zones in both the Northern and Southern Hemispheres (Fig. 7, 8b).…”
Section: Discussionmentioning
confidence: 99%
“…6a; e.g. Serreze and Barry, 2011;Hill et al, 2014), OVL effect dominates the meridional warming contrast. Note that CO 2 is the largest contributor to the global mean Pliocene warming (Sect.…”
Section: Regional Changes In Temperature and Precipitationmentioning
confidence: 99%
“…Increasing albedo over North America middle latitude and eastern Siberia due to change in vegetation (boreal forest in modern but grassland in the Pliocene; Fig. 1; Haywood et al, 2013;Hill et al, 2014), a part of OVL effect, contributes to the regional difference in the SAT change (Figs. 5c, 7c).…”
Section: Regional Changes In Temperature and Precipitationmentioning
confidence: 99%
See 2 more Smart Citations